Comparison of gene expression in cynomolgus monkeys with preclinical type II diabetes induced by different high energy diets. Issue 1 (20th February 2019) - Jin, Li‐Sha; Rao, Jun‐Hua; Zhang, Li‐Biao; Ji, Fang; Zhang, Yan‐Chun; Hao, Xiang‐Fen; Peng, Bai‐Lu; Liu, Xiao‐Ming; Sun, Yun‐Xiao
Abstract: Background: Cynomolgus disease models that are similar to the preclinical stage of human type 2 diabetes mellitus (T2DM) were established by feeding middle‐aged cynomolgus monkeys different high energy diets to study the differential expression of diabetes‐related genes. Methods: A total of 36 male monkeys were randomly divided into four groups and fed human diets with high sugar, high fat, double high sugar and fat, and a normal diet. The preclinical diabetes phase was determined by monitoring the metabolic characteristic indices and the results of oral glucose tolerance tests (OGTT). The mRNA expression of 45 diabetes‐related genes in peripheral blood leukocytes was analyzed using real‐time PCR. Results: A total of 22, 25, and 21 genes were significantly up‐regulated ( P  <   0.05) and 5, 7, and 5 genes were significantly down‐regulated ( P  <   0.05) in the above three induced groups, respectively, compared with the control group. Of the 45 tested genes, the expression profiles of 21 genes were consistent. Most of the expression levels in the double high sugar‐and‐fat individuals were slightly lower than those in the high glucose and high fat groups, although the expression patterns of the three groups were essentially similar. Conclusion: The different high energy diets all induced diabetes and shared some phenotypic properties with human T2DM. Most of the expression patterns of the related genes were identical. The gene expression profiles could be used as references for the study of early diagnostic indicators and T2DM pathogenesis.